MMP14 Cleavage of VEGFR1 in the Cornea Leads to a VEGF-Trap Antiangiogenic Effect - Han, Kyu-Yeon (Invest Ophthalmol Vis Sci, 2015)
PURPOSE: To determine the possible antiangiogenic effect of metalloproteinase (MMP) 14 cleavage of vascular endothelial growth factor receptor 1 (VEGFR1) in the cornea. METHODS: Recombinant mouse (rm) VEGFR1 was incubated with various concentrations of recombinant MMP14 to examine proteolysis in vitro. The reaction mixture was analyzed by SDS-PAGE and stained with Coomassie blue. The fragments resulting from rmVEGFR1 cleavage by MMP14 were subjected to Edman degradation, and the amino acid sequences were aligned with rmVEGFR1 sequences. Surface plasmon resonance was used to determine the equilibrium dissociation constant (K(D)) between MMP14 and rmVEGFR1. The K(D) value of rmVEGFR1 and the 59.8-kDa cleavage product binding to VEGF-A(165) was also determined. Cell proliferation assays were performed in the presence of VEGF-A(165) plus the 59.8-kDa VEGFR1 fragment or VEGF-A(165) alone. RESULTS: Matrix metalloproteinase 14 binds and cleaves rmVEGFR1 to produce 59.8-kDa (N-terminal fragment, Ig domains 1–5), 35-kDa (C-terminal fragment containing IgG and His-tag), and 21-kDa (Ig domains 6–7) fragments. The 59.8-kDa fragment showed binding to VEGF-A(165) and inhibited VEGF-induced endothelial cell mitogenesis. CONCLUSIONS: Our findings suggest that VEGFR1 cleavage by MMP14 in the cornea leads to a VEGF-trap effect, reducing the proangiogenic effect of VEGF-A(165), thereby reducing corneal angiogenesis.